2022
DOI: 10.3390/nano12060947
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Amine-Functionalized Nano-Silica via Sol-Gel Assisted by Reverse Micelle Microemulsion for Environmental Application

Abstract: Amine modified nano-silica was prepared via a one-pot route and under very mild conditions in water in oil microemulsion with a non-ionic surfactant to study the effect of changing the amount of N-[3-(Trimethoxysilyl)propyl]ethylenediamine (DA) added to the synthesis mixture on the characteristics of the obtained nanocomposite such as morphology, crystallinity, surface charge, particle size, surface area, and accordingly the effect of all of these factors on the efficiency of the nanocomposite for the removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Lu et al (2018) reported a decrease in the adsorption capacity of MO on the surface of biochar at a pH higher than 7 due to the deprotonation of the surface and, thus, repulsive force with the anionic dye [ 22 ]. Da’na et al (2022) applied the amine-modified silica with a pH ZPC around 7 to adsorb Zn 2+ by controlling the solution pH at 7.5, which makes the adsorbent surface negatively charged, and they reported 100% removal of this cation [ 32 ]. Khalaf et al (2019) applied ZnO nanoparticles to adsorb anionicbytionic dyes by controlling the surface charge of the adsorbent [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lu et al (2018) reported a decrease in the adsorption capacity of MO on the surface of biochar at a pH higher than 7 due to the deprotonation of the surface and, thus, repulsive force with the anionic dye [ 22 ]. Da’na et al (2022) applied the amine-modified silica with a pH ZPC around 7 to adsorb Zn 2+ by controlling the solution pH at 7.5, which makes the adsorbent surface negatively charged, and they reported 100% removal of this cation [ 32 ]. Khalaf et al (2019) applied ZnO nanoparticles to adsorb anionicbytionic dyes by controlling the surface charge of the adsorbent [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, slower diffusion is expected to take place at pH = 3.5 with lower removal efficiency. To confirm the rule of amine in improving the surface charge of the adsorbent, other experiments were performed with silica nanoparticles (S), which have a pH ZPC of 2.0 as shown in Figure 1 f [ 32 ]. Thus, at both pH values, the surface will be negatively charged as proposed in Scheme 1 and a repulsive force is expected to prevent the reach of the MO molecules to the adsorption sites on the surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of dislocation lines per unit volume is defined by the dislocation density (δ). It represents the number of defects in the film and is estimated as [38]:…”
Section: Structural Propertiesmentioning
confidence: 99%
“…[23][24][25] Silica (SiO 2 ) is also an extensively studied porous material having outstanding properties like high-temperature stability, larger surface area, and excessive absorption capacity, all of which are important factors for catalysis. [26][27][28] Silica is naturally transparent, and ceria's lattice parameter (0.541 nm) closely resembles that of silica. Due to these properties, ceria was chosen for making composite with SiO 2 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%